Achilles Injury and Access to Care in South Florida. Issue 4 (22nd October 2020) - Boden, Allison; Geller, Joseph S.; Granger, Caroline; Summers, Spencer H.; Kaplan, Jonathan R.; Aiyer, Amiethab A.
Category: Hindfoot; Ankle Introduction/Purpose: Achilles Tendon (AT) rupture is the most common tendon rupture in the lower extremity with an incidence of 2.1 AT ruptures per 100, 000 person years. Due to the non-emergent nature of this injury, a delay in presentation may occur leading to delays in diagnosis and treatment; which may alter both nonoperative and operative management. Health insurance status may directly impact time to presentation for many patients. To our knowledge, no study has evaluated the effect of insurance status on delay in diagnosis and treatment of AT rupture. Methods: From December 2013 to December 2018, 89 patients with AT ruptures who underwent surgical management were identified by CPT code in a dual-institution retrospective chart analysis. Demographic and injury-specific data were obtained with attention to the date of injury, date of diagnosis, location of initial presentation (clinic vs. emergency room), and number of medical visits. A univariate two tail t test was used to compare various groups. Statistical significance was set at p < 0.05 to determine the effects of insurance type on the time to diagnosis and treatment of acute AT ruptures. Results: When compared to adequately insured patients (private and Medicare), underinsured patients (uninsured and Medicaid) experienced a significantly greater time from the date of: injury to first clinic visit (14.5 days versus 5.2 days, p < 0.001), first clinic visit to surgery (34.6 days versus 4.8 days, p < 0.002), injury to surgery date (48.9 days versus 9.8 days, p < 0.001), initial presentation to when magnetic resonance imaging (MRI) was obtained (48.1 days versus 1.9 days, p < 0.002), and initial presentation to diagnosis (22.8 days versus 1.71 days, p < 0.029). Conclusion: Disparities in access to care are intimately related to insurance status. Uninsured and medicaid patients are subject to institutional delays and decreased access to care when compared to patients with private insurance. Under and uninsured patients are significantly more likely to present to the emergency department for their initial visit, potentially resulting in increased healthcare costs. Emergency department visits as well as difficulty in obtaining an appointment with an orthopedic surgeon may directly contribute to delay in diagnosis.